TRANSFORMING DOCTORAL EDUCATION: QUALITY ASSURANCE IN SUPERVISION PROCESSES AT ZOU - Nyathi-Moyo , Dr. Grace (Top Educational Review Journal (TERJ), 2023)
This study addresses the challenges of time-to-degree completion among doctoral candidates, recognizing that only a fraction successfully finish their studies within a reasonable timeframe. Current research indicates that merely half of these candidates manage to complete their programs, with an even smaller subset accomplishing their research projects within three years. A significant factor contributing to these poor completion rates is the supervision process, which plays a pivotal role in doctoral education. European University Institute (2017) underscores the critical impact of research supervision on the success of PhD candidates, highlighting the pivotal nature of this aspect. Furthermore, effective supervision is not only a crucial pedagogical component but also a means of ensuring positive graduate outcomes and timely program completion. This aligns with the assertion made by LERU (2010) that adept supervision is instrumental in achieving optimal results and avoiding wastage of both time and resources. A crucial perspective that emerges from this context is the alignment between supervision, institutional strategy, and the outcomes desired for both the academic institution and the doctoral candidates. By fulfilling the institution's strategic objectives, quality supervision contributes to enhancing the institution's reputation while simultaneously supporting candidates in their timely completion of the program. In this vein, Zimbabwe Open University (ZOU) has implemented a comprehensive quality assurance framework for the supervision process in doctoral education. The primary aim is to instill confidence among stakeholders that the supervision process is meticulously planned and executed, thereby enhancing the overall educational experience for candidates. The study also emphasizes the continuous improvement of the doctoral education supervision process as a means of enhancing its quality indicators. By actively assessing and refining the supervision process, institutions like ZOU strive to boost completion rates and promote positive outcomes for candidates. In conclusion, the research delves into the multifaceted nature of doctoral education, highlighting the criticality of effective supervision in ensuring both institutional and candidate success. By acknowledging the challenges and proactively addressing them, educational institutions can pave the way for higher completion rates and a more fruitful doctoral education experience